Attentional biases for threat after fear-related autobiographical recall. Issue 1 (2nd January 2018) - Sagliano, Laura; Trojano, Luigi; Di Mauro, Valentina; Carnevale, Paola; Di Domenico, Marina; Cozzolino, Caterina; D'Olimpio, Francesca
ABSTRACT: Background : Previous studies suggested that affective state could enhance stimulus salience and modulate attention allocation for mood-congruent information, but contrasting data have been reported on the effects of mood induction on attentional biases for threat (ABTs) in non-clinical individuals. Objective : We aimed to assess whether laboratory-induced negative mood can increase individuals' tendency to allocate attention on threatening stimuli, thus determining a difficulty in attentional disengagement from threat. We also aimed at assessing whether level of trait anxiety could modulate the effect of mood induction on attentional biases. Methods : We used an autobiographical episode recall procedure for mood induction (fear, happiness and neutral episode recall), and an exogenous cueing task with threatening and non-threatening images to assess attentional biases in 120 undergraduate students. Results: Participants showed a significant difficulty in disengaging attention from threat after recalling fear-related episodes, independently from their trait anxiety level. Conclusions: These findings clarify that the ABTs are not exclusive to anxiety disorders or high trait anxiety individuals, and could also arise in non-clinical individuals in a fearful context.